METHOD OF MOVING OBJECT DETECTION IN THE VIDEO - К. А. Volkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis of methods of moving objects detection in video is done. The window method of bound rectangles allocation of moving objects, based on integral matrix of binary flags is proposed. A comparative test of the proposed method is done.